Pengembangan Media E-Comel (Komik Melayu Digital) Untuk Meningkatkan Perilaku Moral Anak Usia 5-6 Tahun - Nadia Ramona; Rita Kurnia; Zulkifli N (Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to describe the process and learning outcomes through the application of the use of E-Comel media (digital Malay comics) which can improve the moral behavior of children aged 5-6 years. The type of research used is research and development (Research and Development). The steps taken are potential and problems, data/information collection, product design, product design validation, design revision, product manufacture, and product trials. Data collection techniques by observation, distributing questionnaires, and analysis of documentation. The instrument used was a questionnaire for validating E-COMEL media from media experts, material experts, linguists and educators. The data analysis technique used is a quantitative descriptive analysis technique by using the experimental method. In the study, the validation of material experts was obtained for 97.92%